A laser-induced fluorescence spectroscopic study of organic matter in a Brazilian Oxisol under different tillage systems - Gonzalez-Perez, Martha; Milori, Debora M. B. P.; Colnago, Luiz A.; Martin-Neto, Ladislau; Melo, Wanderley J. (Elsevier B.V., 2007)
Laser-induced fluorescence (LIF) spectroscopy has been proposed as new method for determining the degree of humification of organic matter (OM) in whole soils. It can be also used to analyze the OM in whole soils containing large amounts of paramagnetic materials, and which are neither feasible to Electron Paramagnetic Resonance (EPR) nor to C-13 Nuclear Magnetic Resonance (NMR) spectroscopy. In the present study, 3 LIF spectroscopy was used to investigate the OM in a Brazilian Oxisol containing high concentration of Fe+3. Soil samples were collected from two areas under conventional tillage (CT), two areas under no-till management (NT) and from a non-cultivated (NC) area under natural vegetation. The results of LIF spectroscopic analysis of the top layer (0-5 cm) of whole soils showed a less aromatic OM in the non-cultivated than in the cultivated soils. This is consistent with data corresponding to HA samples extracted from the same soils and analyzed by EPR, NMR and conventional fluorescence spectroscopy. The OM of whole soils at 5-10 and 10-20 cm depth was also characterized by LIF spectroscopy.Analysis of samples of NT and NC soils showed a higher OM aromatic content at depth. This is a consequence of the accumulation of plant residues at the soil surface in quantities that are too large for microorganisms to metabolize fully, thus, resulting in less aromatic or less hurnified humic substances. In deeper soil layers, the input of residues was lower and further decomposition of humic substances by microorganisms continued, and the aromaticity and degree of humification increased with soil depth. This data indicates that the gradient of humification of OM in the NT soil was similar to those observed in natural soils. Nevertheless, the degree of humification of the OM in the soils under no-till management varied less than that corresponding to non-cultivated soils. This may be because the former have been managed under these practices for only 5 years, in contrast to the continuous humification process occurring in the natural soils. on the other band, LIF spectroscopic analysis of the CT soils showed less pronounced changes or no change in the degree of humification with depth. This indicates that the ploughing and harrowing involved in CT lead to homogenization of the soil and thereby also of the degree of humification of OM throughout the profile. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: soil organic matter; humic acids; laser induced fluorescence; EPR; NMR